PENGARUH MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF MODEL CANVA PADA KOMPETENSI MAHASISWA TEKNIK BANGUNAN - Aldi Restu Putra (CV. ADIBA AISHA AMIRA, 2024)
This study aims to examine the effect of using interactive multimedia-based learning media Canva model on the competence of building engineering students. Data was obtained from analyzing related articles that discuss the application of Canva media in building engineering learning. The research method uses literature review, which involves reviewing and critically evaluating literature sources relevant to the research topic. The research results were written through a qualitative descriptive approach. Studies conducted by various researchers show that the use of the Canva model as an interactive multimedia-based learning media has a significant positive impact on improving student competence in understanding building engineering material. This shows that the use of interactive multimedia technology, such as Canva, can be an effective alternative in improving student competence in the field of building engineering.